Comparison of Radiation Exposure Between Anterior, Lateral, and Posterior Interbody Fusion Techniques and the Influence of Patient and Procedural Factors. Issue 23 (1st December 2021) - Striano, Brendan M.; Xiong, Grace X.; Lightsey, Harry M.; Crawford, Alexander M.; Pisano, Alfred J.; Schoenfeld, Andrew J.; Simpson, Andrew K.
Abstract : Study Design: Retrospective cohort. Objective: The aim of this study was to elucidate the relative influence of multiple factors on radiation usage for anterior, lateral, and posterior based lumbar interbody fusion techniques. Summary of Background Data: There has been substantial global growth in the performance of lumbar interbody fusions, due to evolution of techniques and approaches and increased attention to sagittal alignment. Utilization of intraoperative imaging guidance has similarly expanded, with a predominance of fluoroscopy and consequent increased radiation exposure. There have been no larger-scale studies examining the role of patient and procedural factors in driving radiation exposure across different interbody techniques. Methods: We used a clinical registry to review all single-level lumbar interbody fusions performed between January 2016 and October 2020. Operative records were reviewed for the amount of radiation exposure during the procedure. Patient age, biologic sex, body mass index (BMI), operative surgeon, surgical level, surgical time, and fusion technique were recorded. Multivariable adjusted analyses using negative binomial regression were used to account for confounding. Results: We included 134 interbody fusions; 80 performed with a posterior approach (TLIF/PLIF), 43 via an anterior approach (ALIF) with posterior pedicle fixation, and 9 performed with a lateral approach (LLIF/XLIF). Average radiation per case was 136.4 mGy (SE 17.3) for ALIF, 108.6 mGy (16.9) for LLIF/XLIF, and 60.5 mGy (7.4) for TLIF/PLIF. We identified lateral approaches, increased BMI, minimally invasive techniques, and more caudal operative levels as significantly associated with increased radiation exposure. Conclusion: We identified several novel drivers of radiation exposure during interbody fusion procedures, including the relative importance of technique and the level at which the fusion is performed. More caudal levels of intervention and lateral based techniques had significantly greater radiation exposure. Level of Evidence: 4 Abstract : Increasing use of interbody fusion techniques has led to greater utilization of intra-operative imaging modalities without detailed understanding of the ramifications of different interbody fusion techniques on radiation. Our study identified novel factors associated with increased radiation usage including lateral technique and more caudal levels.